Answer:
[tex]g(x) = 4(x - 2)^2 -9[/tex]
Step-by-step explanation:
Given
[tex]g(x) = 4x^2 - 16x + 7[/tex]
Required
Complete the square
Rewrite so that [tex]x^2[/tex] has 1 coefficient
[tex]g(x) = 4(x^2 - 4x) + 7[/tex]
Take half of the coefficient of x
[tex]\frac{4}{2} = 2[/tex]
Square the result
[tex](\frac{4}{2})^2 = 2^2[/tex]
[tex](\frac{4}{2})^2 = 4[/tex]
Add and subtract the result in the bracket
[tex]g(x) = 4(x^2 - 4x + 4 - 4) + 7[/tex]
Expand the bracket to remove -4
[tex]g(x) = 4(x^2 - 4x + 4) - 16 + 7[/tex]
[tex]g(x) = 4(x^2 - 4x + 4) -9[/tex]
Expand the bracket
[tex]g(x) = 4(x^2 - 2x -2x+ 4) -9[/tex]
Factorize
[tex]g(x) = 4(x(x - 2) -2(x-2)) -9[/tex]
Factor out x - 2
[tex]g(x) = 4((x - 2)(x-2)) -9[/tex]
Express as square
[tex]g(x) = 4(x - 2)^2 -9[/tex]